Analysis of transient fluid slosh in partly-filled tanks with and without baffles: Part 1 – model validation. (12th October 2010) - Yan, G.R.; Rakheja, S.; Siddiqui, K.
Fluid slosh in partly-filled tanks is modelled as a two-phase flow, and solved using a Navier-Stokes (NS) solver, while the interface of two fluids is tracked using the VOF technique. The fluid slosh in cleanbore and baffled scale model tanks was further characterised in the laboratory, under different fill levels and excitations. The validity of the slosh model, reduced to the scale model tank, was evaluated using the measured data in terms of fundamental slosh frequency, and transient and steady-state slosh forces and moments over a wide range of conditions such as the tank configuration, fill level and acceleration excitation. The model results showed reasonably good agreements with the measured data, irrespective of tank configuration, fill level and the acceleration excitation. It is concluded that the dynamic fluid slosh model can effectively predict the forces and moments associated with 3-D fluid slosh observed under lateral or longitudinal excitations. The fluid slosh model may thus be integrated to the vehicle model to investigate partly-filled tank vehicle responses and the role of baffles. The slosh forces and moments responses of a full-size tank model were subsequently evaluated using FLUENT software.